Behaviour of Traders And Manufacturers In The Use Of Formalin In Wet Noodle And Tofu In Jakarta - Galih Prima Arumsari; Tri Krianto; Bambang Wispriyono (Jurnal Kesehatan Masyarakat Andalas, 2016)
Formalin has been used widely in tofu and wet noodle as a preservative in Indonesia even it has been classified as a confirmed carcinogenic agent. The aim of this study is to analyze the behavior of traders and producers of tofu and wet noodle in the use of formalin in its products in DKI Jakarta. This study was conducted in March-June 2015 by using a qualitative method, descriptive study design, through literature study, interview and observation. The informants are producers and traders of wet noodles and tofu. Formalin was examined by Rapid Test Kit analysis. The results showed that knowledge, attitudes, perceptions of formalin; facilities and infrastructure, production and preservative; punishments, counseling, social support, income, and communication strategy played important roles in behavior of using of formalin. Communication and supervisory for public, traders, manufacturers are still limited. The distribution of formalin which is conducted by the government has not run optimally yet. Counseling and development to the community, traders and manufacturers are limited. Supervision of distribution of formalin has not worked optimally yet. As the recommendation to the number of parties to do research on safe preservatives, intensification of coaching traders and manufacturers as well as consumer empowerment should be done.